The Correlation Between Implementation of the Merdeka Curriculum and Students’ Learning Independence in Science Learning Among Eighth-Grade Students at SMP Negeri 48 Samarinda: Hubungan Implementasi Kurikulum Merdeka dengan Kemandirian Belajar Siswa dalam Pembelajaran IPA - Riskhy, Friska; Herliani; Maasawet, Elsje T.; Makkadafi, Suparno P. (PendIPA Journal of Science Education, 2025)
This study aimed to determine the relationship between the implementation of the Merdeka Curriculum and students’ learning independence in Science subjects among eighth-grade students at SMP Negeri 48 Samarinda. This research employed a quantitative approach with a correlational method. The sample consisted of 100 students selected using stratified random sampling from a total population of 128 students. Data was collected using a closed-ended questionnaire based on a Likert scale. The data analysis techniques included normality testing, linearity testing, and Pearson Product Moment correlation. The results showed that the implementation of the Merdeka Curriculum was categorized as "Very Good" with a percentage score of 81.60%, while students’ learning independence was categorized as "Good" with a percentage score of 79.77%. The correlation test indicated a positive and significant relationship between the implementation of the Merdeka Curriculum and students' learning independence, with a correlation coefficient (r) of 0.685 and a significance value of 0.000 (< 0.05). Additionally, the coefficient of determination showed that the Merdeka Curriculum contributed 46.90% to students' learning independence. These findings suggest that the more optimally the Merdeka Curriculum is implemented, the higher the level of students' learning independence. This research is expected to serve as a reference for teachers and school stakeholders in enhancing the quality of science learning that fosters student independence.